Collective physician perspectives on non-oral medication approaches for the management of clinically relevant unresolved issues in Parkinson's disease: Consensus from an international survey and discussion program. Issue 10 (October 2015) - Odin, P.; Ray Chaudhuri, K.; Slevin, J.T.; Volkmann, J.; Dietrichs, E.; Martinez-Martin, P.; Krauss, J.K.; Henriksen, T.; Katzenschlager, R.; Antonini, A.; Rascol, O.; Poewe, W.; et al.
Abstract: Navigate PD was an educational program established to supplement existing guidelines and provide recommendations on the management of Parkinson's disease (PD) refractory to oral/transdermal therapies. It involved 103 experts from 13 countries overseen by an International Steering Committee (ISC) of 13 movement disorder specialists. The ISC identified 71 clinical questions important for device-aided management of PD. Fifty-six experts responded to a web-based survey, rating 15 questions as 'critically important;' these were refined to 10 questions by the ISC to be addressed through available evidence and expert opinion. Draft guidance was presented at international/national meetings and revised based on feedback. Key take-home points are: Patients requiring levodopa >5 times daily who have severe, troublesome 'off' periods (>1–2 h/day) despite optimal oral/transdermal levodopa or non-levodopa-based therapies should be referred for specialist assessment even if disease duration is <4 years. Cognitive decline related to non-motor fluctuations is an indication for device-aided therapies. If cognitive impairment is mild, use deep brain stimulation (DBS) with caution. For patients who have cognitive impairment or dementia, intrajejunal levodopa infusion is considered as both therapeutic and palliative in some countries. Falls are linked to cognitive decline and are likely to become more frequent with device-aided therapies. Insufficient control of motor complications (or drug-resistant tremor in the case of DBS) are indications for device-aided therapies. Levodopa-carbidopa intestinal gel infusions or subcutaneous apomorphine pump may be considered for patients aged >70 years who have mild or moderate cognitive impairment, severe depression or other contraindications to DBS. Highlights: Gaps in knowledge exist regarding device-aided therapies for Parkinson's disease. 'Navigate PD' aimed to answer common questions regarding device-aided therapies. We present practical guidance for device-aided therapies in Parkinson's disease.